The war beyond - Stewart, Andrea (Andrea G.) (Stewart, Andrea (Andrea G.). Hollow covenant, 2025)
In this thrilling sequel to the Sunday Times bestseller The Gods Below, loyalties will be tested, long-lost secrets will be revealed, and two sisters will face each other on the battlefield as the war between the gods ignites. Hakara risked her life to find her long-lost sister Rasha, only to lose her all over again. Now she and her Unanointed rebels hunt for the shapeshifter Lithuas, knowing that defeating her would strike a blow to the plans of the tyrant god Kluehnn. Rasha once longed to be reunited with Hakara. No longer. Now she is a Godkiller and proud to serve Kluehnn's divine will. Yet she also harbours doubts about Kluehnn's teachings. When she is sent to destroy Hakara and her allies, Rasha will have to decide where her loyalty truly lies. As the two sisters hurtle towards a bloody reunion, Sheuan continues her shadowy games of intrigue to uncover the secret that killed her father, while her cousin Mullayne seeks the tomb of Tolemne. There, Mull believes he'll find the answers he desires.